2012
DOI: 10.2139/ssrn.1319786
|View full text |Cite
|
Sign up to set email alerts
|

Mutual Fund's R2 as Predictor of Performance

Abstract: Abstract:We propose that fund performance is predicted by its R 2 , obtained by regressing its return on the Fama-French-Carhart four benchmark portfolios. Lower R 2 , or higher idiosyncratic risk relative to total risk, measures selectivity or active management. We show that lagged R 2 has significant negative predictive coefficient in predicting alpha or Information Ratio. This is consistent with Cremers and Petajisto's (2008) results on the effect of selectivity. Funds ranked into lagged lowest-quintile R 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
159
2
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 108 publications
(186 citation statements)
references
References 49 publications
23
159
2
2
Order By: Relevance
“…Finally, also using regression models, the main determinants of the R 2 of the funds were calculated, by investigating the explanatory power of characteristics such as time under current management, size, age, expenses, turnover, and style. Th e results from Amihud and Goyenko (2013) confi rm these relationships and allow it to be concluded that there is eff ectiveness in the methodology. Th e portfolio of funds with the lowest R 2 and highest performance presented signifi cantly better returns than those of the other portfolios.…”
Section: Introductionmentioning
confidence: 57%
See 4 more Smart Citations
“…Finally, also using regression models, the main determinants of the R 2 of the funds were calculated, by investigating the explanatory power of characteristics such as time under current management, size, age, expenses, turnover, and style. Th e results from Amihud and Goyenko (2013) confi rm these relationships and allow it to be concluded that there is eff ectiveness in the methodology. Th e portfolio of funds with the lowest R 2 and highest performance presented signifi cantly better returns than those of the other portfolios.…”
Section: Introductionmentioning
confidence: 57%
“…This study is based on the methodology created by Amihud and Goyenko (2013) for predicting fund performance based on level of selectivity. Th e methodology supports the hypothesis that the greater a fund's level of activity is, the better its performance will be.…”
Section: Predicting Performance Based On the Rmentioning
confidence: 99%
See 3 more Smart Citations